ANALISIS PERSEPSI KONSUMEN TERHADAP KEPUASAN DALAM MENCIPTAKAN LOYALITAS KONSUMEN PADA TOKO BUKU GRAMEDIA BIGMALL SAMARINDA - Syahdan Basirang; Dian Irma Aprianti (University of Widya Gama Mahakam Samarinda, 2021)
Tested simultaneously from the variable Dimensions of Products, Promotion, Distribution, Facilities and Infrastructure, and Prices for consumer satisfaction, the F value is shown to be 12.156 with a significant value of 0.000 and satisfaction with Loyalty with an F value of 43.995 with a significant level of 0.000. Judging from the results of the t test, it can show that consumer perceptions of the promotion dimension have no significant effect on consumer satisfaction with the t value of 1.311 smaller than t table 1.661, consumer perceptions of the distribution dimension have no significant effect on satisfaction with the t value of 1.293 smaller than t table 1.661, Consumer perceptions of the promotion dimension do not have a significant effect on consumer satisfaction with a t value of 1.593 smaller than t table 1.661, Consumer perceptions of the dimensions of physical supporting infrastructure have no significant effect on consumer satisfaction with a value of t count 1.205 smaller than t table 1.661, Consumer perception dimensions Price has a significant effect on consumer satisfaction with the value of t count 3.997 is greater than t count of 1.661. And satisfaction has a significant effect on consumer loyalty with t count 4.258 greater than t table 1.661.